Determinants of COVID-19 vaccination acceptance based on the novel Omale INDEPT FORCIS Framework and recommendations for subsequent pandemics: a qualitative study among community members in Ebonyi state, Nigeria - Ugwu I. Omale; Azuka S. Adeke; Onyinyechukwu U. Oka; Cordis O. Ikegwuonu; Osarhiemen Iyare; Olaedo O. Nnachi; Victor U. Uduma; Chidinma I. Amuzie; Glory E. Nkwo; Ugochi I. A. Nwali; Okechukwu O. Ukpabi; Ifeyinwa M. Okeke; et al. (International Journal for Equity in Health)
Abstract Background The unprecedented COVID-19 pandemic has become an endemic disease of global public health importance. Mass COVID-19 vaccination has been an essential global control strategy amidst challenges of limited acceptance. Because of globalization, COVID-19/similar diseases vaccination acceptance and the determinants in any particular setting are important global public health issues. Using a novel and pragmatic framework, this study explored determinants of COVID-19 vaccination acceptance among community members during the pandemic in Ebonyi state, Nigeria, and made policy-relevant recommendations on how to increase vaccination acceptance in subsequent outbreaks/pandemics. Methods This qualitative study was based on the novel and pragmatic Individual Experiences and Perceptions and Complacency, Confidence, Convenience, and Compulsion (Four ‘Cis’) Determinants of Vaccination Acceptance Conceptual Framework – Omale INDEPT FORCIS Framework. On April 26 and 27, 2022, 20 semi-structured face-to-face focus group discussions were conducted in local language and pidgin English with 100 purposively selected consenting/assenting community members aged 15 years and above who had resided in the community for at least one year. Data was analysed using deductive (with some inductive) thematic analytic approach. Results The many, diverse, and significant determinants of COVID-19 vaccination acceptance found were factors that were individual-related (individual experiences and perceptions and knowledge about COVID-19, COVID-19 vaccine/vaccination, and the vaccination process/system, sociodemographic, individual’s condition (e.g. pregnancy)); COVID-19-related (factuality, transmissibility, frequency, severity, fatality); COVID-19 vaccine/vaccination-related (safety/side-effects, effectiveness, speedy production); COVID-19 vaccination process/system-related (real availability/accessibility); family, group, and other individual-related (experiences and perceptions and actions); and broader local, national, international, and global (LONING) context-related (socio-political, economic, historic, health system factors). The broader LONING contextual factors included the unprecedented disinformation/conspiracy theories, non-sustained COVID-19 risk/behaviour change communication, enforcement and non-enforcement or termination of peculiar control policies/measures (lockdowns, social/physical distancing, use of face mask etc.), mandatory COVID-19 vaccination policies, provision of incentives, past experiences regarding the Ebola viral disease outbreak, (un)trustworthiness of the Nigerian health system and her international/global partners, and the (un)trustworthiness of the governments in Nigeria and bad/good governance, inclusive of the failure of the Ebonyi state government to distribute the COVID-19 palliatives to the people during the lockdowns. Conclusion The evidence illuminates complex and interrelated, specific underlying, and peculiar policy-relevant LONING determinants of COVID-19 vaccination acceptance and emphasizes the need for concerted and comprehensive LONING strategies (involving all the relevant LONING stakeholders/policy makers) in addressing these determinants to increase vaccination acceptance among community members in subsequent outbreaks/pandemics in Ebonyi state/Nigeria and similar settings.